Churg-Strauss Syndrome Accompanied by Acute Coronary Syndrome in the Absence of Coronary Atherosclerosis - Demet Menekşe GEREDE; Orhan KÜÇÜKŞAHİN and Elif Ezgi ÜSTÜN and Kerim ESENBOĞA and Sibel TURHAN (Archives of Rheumatology, 2013)
Herein, we report a 35-year-old female case who was admitted to our emergency department with chest pain along with a past history of asthma and pleural effusion. Her laboratory findings revealed high levels of cardiac biomarkers [troponin I (TnI) and creatine kinase-MB isoenzyme (CK-MB)] without significant ST segment and T wave (ST-T) changes in the electrocardiogram. Transthoracic echocardiography showed hypokinesis of the anterior wall with an ejection fraction of 48% and minimal pericardial effusion. Coronary arteriography revealed a distally occluded left anterior descending coronary artery. Churg-Strauss syndrome with acute coronary syndrome was diagnosed. The patient was administered systemic corticosteroid therapy. Our patient subsequently made an uneventful recovery.